Implementasi Program TPQ Ceria dalam Meningkatkan Kemampuan Membaca Al-Qur’an dan Pembentukan Karakter Islami pada Anak di Desa Mlese, Cawas, Klaten - Maulana M Nur Miqdad; Aldira Naila Putri; Alfiana Lail Dayanti K; Ilham Firmansyah Mahfudz; Intan Nuraini; Marghareta Willy Angjela; Misye Belakartika; Muhammad Wafiqul Arzaqi; Nerissa Rahmania Putri; Royyan Alkhoiri; Salma Salsabila Khusna; Sherly Novita Sari; Reno Nurdiyanto (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The ability to read the Qur'an and the development of Islamic character are essential aspects of children's education that should be fostered from an early age. However, several challenges remain, including limited Qur'anic reading proficiency, inadequate understanding of tajwid (rules of Qur'anic recitation), and the suboptimal internalization of Islamic values in daily life. The Cheerful Qur'anic Learning Center (Taman Pendidikan Al-Qur'an/TPQ) Program in Mlese Village, Cawas District, Klaten Regency, was developed as a community service initiative to improve children's Qur'anic reading skills while fostering Islamic character. This study aims to analyze the implementation of the Cheerful TPQ Program in enhancing children's Qur'anic reading ability and Islamic character development. The program employed a Service-Learning approach consisting of four stages: preparation, service, reflection, and evaluation. Data were collected through observation, documentation, and reflective activities conducted throughout the program. The findings indicate that the Cheerful TPQ Program positively contributed to improving participants' reading fluency, accuracy in pronouncing makharij al-huruf (points of articulation of Arabic letters), basic understanding of tajwid, and self-confidence in reciting the Qur'an. Furthermore, the program supported the development of Islamic character through the habituation of daily prayers, memorization of prayers and short Qur'anic chapters, basic fiqh instruction, and the cultivation of religious values. Therefore, the Cheerful TPQ Program represents an effective form of community-based non-formal education in enhancing children's Qur'anic reading competence while supporting the development of their Islamic character.